The role of entrepreneurship in achieving competitive advantage - an exploratory study of the opinions of a sample of managers in private Iraqi banks - صلاح الدين عواد كريم الكبيسي,; إياد خالد مهدي الجوراني, (Iraqi Journal for Administrative Sciences, 2025)
The purpose of this search is know the Role of entrepreneurial business in competitive advantage of for Iraqi private banks, through relationship and effect, The present search is applied on (70) subjects selected randomly from (10) Iraqi private banks. Questionnaire , interviews, and the researcher\'s personal observations are all regarded as strategies for data collection. Many statistical procedures are used ,like variance, Multiple Regression. The main findings is :There are asignifinct relationship and effect of the entrepreneurial business dimensions in competitive advantages, The importance recommendations of this study was all relevant to the processes adopted by Iraqi private banks in implementing creative entrepreneurial business dimensions , in creating positive changes in the competitive strategy of time , speed, achievement of customers\' services, and its relevance in increasing more market share.